A simplified shear model for reinforced concrete elements subjected to reverse lateral loadings - Rodrigues, H.
The response of reinforced concrete elements to earthquake loads can be controlled by bending or shear behaviour, depending on the geometrical characteristics of the elements and on the reinforcement detailing. To represent the shear behaviour, in elements where shear is not negligible, it was developed and implemented in the VisualANL a non-linear shear model. Finally, in this paper are presented and discussed the results of a set of numerical calibration analyses based on tests on full-scale frames.